Supplemental online resources improve data literacy education: Evidence from a social science methods course. - Marco Alcocer; Leonardo Falabella; Alexandra Lange; Nicholas Smith; Maureen Feeley (PLoS ONE)
Despite the importance of data literacy skills for academic and professional careers, learning these skills is a source of stress and difficulty for undergraduate students. This study first introduces an online supplemental instruction resource to support student learning in an introductory data analysis course at a large public university. To evaluate its impact, we conduct a pre-registered double-blind within-subject experiment. Each student is randomly assigned to a subset of the online supplemental instruction modules and takes an exam assessing concepts covered by the course material and supplemented by the modules. Access to the online supplemental instruction modules improves student performance on exam questions, and students who engage with the modules improve exam scores even more. We find no differential impacts based on pre-treatment GPA or underrepresented status, and a post-experiment survey suggests that the online supplemental instruction modules are also well-received by students. This study shows that asynchronous online supplemental instruction resources are a promising way to support student learning in data literacy.